The NFκB Expression on Apical Dental Granuloma: An Immunohistochemistry Analysis - Cilmiaty R; Pribadi N; Rukmo M; Surboyo MDC (Dove Medical Press, 2020)
Risya Cilmiaty,1 Nirawati Pribadi,2 Mandojo Rukmo,2 Meircurius Dwi Condro Surboyo3 1Department of Oral Disease, Faculty of Medicine, Universitas Sebelas Maret, Surakarta, Indonesia; 2Department of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 3Department of Oral Medicine, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, IndonesiaCorrespondence: Nirawati PribadiDepartment of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga. Jalan Prof. Dr. Moestopo 47x, Surabaya 60132, IndonesiaTel +628123292481Email nirawati-p@fkg.unair.ac.idRisya CilmiatyDepartment of Oral Disease. Faculty of Medicine, Universitas Sebelas Maret, Jalan Ir. Sutami No. 36A, Kenthingan, Surakarta 57126, IndonesiaTel +6281227316161Email h_risya@yahoo.co.idBackground: Endodontic treatment on dental caries with dental granuloma on the periapical has the potential to flare. The symptoms of acute flare in dental granuloma are strongly related to the activation of macrophages that produce pro-inflammatory cytokine through nuclear factor kappa B (NFκB). However, the role of NFκB in dental granuloma has not been widely explained.Purpose: To compare NFκB expression in dental granuloma and dental nongranuloma in the periapical of dental caries.Methods: The periapical lesion of dental granuloma and dental nongranuloma was obtained from patients with dental caries who were subjected to tooth extraction. The periapical lesion was confirmed by periapical radiography and then differentiated by histological and immunohistochemistry by analyzing the NFκB expression.Results: Most dental granulomas were found in females (66.67%) between the ages 36 and 45 (61.11%). Dental granuloma showed higher NFκB expression compared to dental nongranuloma lesions in tooth caries (p=0.021).Conclusion: The dental granuloma tissue of dental caries showed an increase in NFκB expression. Understanding the role of NFκB might provide additional insights into the process of periapical lesion development.Keywords: dental granuloma, dental caries, NFκB expression, periapical lesion